„Nadchodzi wielki tebk …”. Edgara Hilsenratha opowieść o ludobójstwie - Karolak, Sylwia (Slavia Occidentalis, 2015)
The author discusses the issue of the presence of the Holocaust in Edgar Hilsenrath’s novel “The Story of the Last Thought”. Hilsenrath is a Holocaust survivor, and that experience allows him to write about the Armenian genocide, but also affects the substance of his book. It turns out that one can notice similarities not only in the causes and process of each of the genocides, but also in the reaction of the world, which was one of silence. The author states that the silence about Armenian genocide has not been broken. This condition is one of the reasons for the absence of books about the Armenian genocide in the consciousness of readers and entire societies.